2022
DOI: 10.3390/ma15082954
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Membrane of Fish Collagen/Gellan Gum Containing Bone Graft Materials

Abstract: The development of a guided bone regeneration (GBR) membrane with non-mammalian fish collagen has the advantage of low risk for transmission of infectious diseases in tissue regeneration. In this work, a fish collagen/gellan gum and bone graft material (FC/GG-BGM) composite GBR membrane were fabricated through solution blending and casting procedures in a vacuum. The membranes were characterized using Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), scanning electron microscopy observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In preclinical studies, Col sponges were able to accelerate bone healing in cranial CSDs in rats. The most frequent source of Col has been cows and pigs; however, new sources, such as fishes and marine organisms, have been recently proposed to overcome religious issues and potential transmission of pathogens . For example, scaffolds made with fish Col mixed with gellan gum and bovine bone particles showed better osteoinductive properties than bovine Col membranes in CSDs in rats . Col mats’ mechanical properties and osteoinductivity have been enhanced by adding calcium phosphate (CaP) or apatite by in vitro mineralization.…”
Section: Biomaterials Employed To Fabricate Scaffolds Suitable For Cm...mentioning
confidence: 99%
“…In preclinical studies, Col sponges were able to accelerate bone healing in cranial CSDs in rats. The most frequent source of Col has been cows and pigs; however, new sources, such as fishes and marine organisms, have been recently proposed to overcome religious issues and potential transmission of pathogens . For example, scaffolds made with fish Col mixed with gellan gum and bovine bone particles showed better osteoinductive properties than bovine Col membranes in CSDs in rats . Col mats’ mechanical properties and osteoinductivity have been enhanced by adding calcium phosphate (CaP) or apatite by in vitro mineralization.…”
Section: Biomaterials Employed To Fabricate Scaffolds Suitable For Cm...mentioning
confidence: 99%
“…These defects can be either small or large, and they always require an efficient and secure treatment to restore bone tissue. Bone grafting has traditionally been the therapy of choice for bone abnormalities [3]. The restricted availability of autologous bone grafts [3], high treatment costs [4], danger of immunological rejection [5], difficulties in bone handling technologies [6], and the possibility of infection and consequences [7] have all contributed to the limited success of bone transplantation [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Bone grafting has traditionally been the therapy of choice for bone abnormalities [3]. The restricted availability of autologous bone grafts [3], high treatment costs [4], danger of immunological rejection [5], difficulties in bone handling technologies [6], and the possibility of infection and consequences [7] have all contributed to the limited success of bone transplantation [3][4][5][6][7]. The current state of the art in treating bone defects is inadequate to provide adequate care for patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…8 and some of them are approved in some countries for clinical use such as a wound dressing and a tympanic membrane. [9][10][11][12] Silk fibroin, extracted from silk fibers, can be constructed into films, sheets, scaffolds, and filaments. The material can be soft to super-hard due to its high malleability and rigidity.…”
Section: Introductionmentioning
confidence: 99%
“…And there are many in vitro studies that reported the potential of clinical use of fish collagen. [9][10][11] Recently, silk fibroin and fish collagen-based materials with a glycerol plasticizer had been fabricated and characterized to overcome the brittleness and low mechanical strength of silk fibroin material for a barrier membrane and to diminish religious restrictions from the mammal sources. 20 The in vitro study showed that the silk fibroin-glycerol and silk fibroin-glycerol-collagen membranes had good physical and mechanical properties with high stiffness 1.5-2.2 times that of the collagen membrane but still yielded sufficient elongation when compared to the collagen membrane, particularly the silk fibroin-glycerolcollagen.…”
Section: Introductionmentioning
confidence: 99%